Test score equating of multiple-choice mathematics items: techniques from characteristic curve of modern psychometric theory - Musa Adekunle Ayanwale (Springer, 2023)
Abstract Examination scores obtained by students from the West African Examinations Council (WAEC), and National Business and Technical Examinations Board (NABTEB) may not be directly comparable due to differences in examination administration, item characteristics of the subject in question, and student abilities. For more accurate comparisons, scores from different assessments or examibations must be equated. In the literature, little is known about using Stocking-Lord and Haebara Item Response Theory (IRT) methods to equalize WAEC and NABTEB mathematics multiple-choice items. The study used a counterbalanced quantitative design for a single group. As a method for dealing with order effects, counterbalancing was used to assess 50 multiple-choice four-option items developed by WAEC and NABTEB for Grade 12 mathematics. The study selected 1210 Grade 12 students who were divided into groups A (647), and B (563). The IRT equating methods were employed to compare the two test forms based on the obtained data. The findings indicate that WAEC and NABTEB have similar construct domains, though WAEC is more difficult, and discriminates better. Further, when placed on the same scale, both tests are comparable. These findings have implications for curriculum redesign, academic performance assessment, and policymaking in the education sector, as well as refuting public perceptions of the credibility and value of these certificates awarded by the testing organizations in Nigeria.